High Molecular Weight λ-Carrageenan Improves the Color Stability of Phycocyanin by Associative Interactions - Buecker, Stephan; Grossmann, Lutz; Loeffler, Myriam; Leeb, Elena; Weiss, Jochen (Frontiers in Sustainable Food Systems, 2022)
Phycocyanin is a protein-chromophore structure present in Arthrospira platensis commonly used as a blue-colorant in food. Color losses of phycocyanin can be reduced by electrostatic complexation with λ-carrageenan. The aim of this study was to investigate the effect of molecular weight (MW) of λ-carrageenan on the color stabilization of electrostatic complexes formed with phycocyanin and λ-carrageenan. Samples were heated to 70 °C or 90 °C at pH 3.0 and stored at 25 °C for 14 days. . The MW of λ-carrageenan was reduced by ultrasound treatments for 15, 30, 60, and 90 min. Prolonged ultrasonication had a pronounced effect on the Mw, which decreased from 2341 kDa to 228 kDa (0 min to 90 min). Complexes prepared with low MW λ-carrageenan showed greater color changes compared to complexes prepared with high MW λ-carrageenan. The MW had no visible effect on color stability on day 0, but green/yellow shifts were observed during storage and after heating to 70 °C. Medium MW showed less color stabilization effects compared to low MW when heated to 70 °C. Moreover, for solutions prepared with ultrasonicated λ-carrageenan, significant hue shifts towards green/yellow, and precipitation were observed after a heat treatment at 90 °C. In addition, the sizes of the complexes were significantly reduced (646 to 102 nm) by using ultrasonicated λ-carrageenan, except for the lowest MW λ-carrageenan when heated to 90 °C. Overall, these findings demonstrated that decreasing the MW of λC had adverse effects on the color stability of PC:λC complexes heated to 70 °C and 90 °C.